Circulating leptin, zinc, and copper levels after extracorporeal circulation - Gormus, ZI; Gormus, N; Baltaci, AK; Halifeoglu, I; Mogulkoc, R (Maghira & Maas Publications, 2005)
OBJECTIVE: The role of leptin in the acute stress response to extracorporeal circulation has been well documented, however, the relationship between leptin and zinc has not been investigated previously. We aimed to research the circulating leptin, zinc, and copper levels before, during, and after the extracorporeal circulation, and effect of preoperative zinc administration to these. METHODS: Twenty patients who were taken to elective coronary artery bypass grafting operations using extracorporeal circulation were taken to this research and divided into two equal groups (n(1), n(2)). In both groups blood samples were taken just before the operation (T0), at the end of operation (T1), and at the first postoperative day (T2). In the second group (n(2)) oral zinc (50 mg, once a day) was administered to patients for 5 days, preoperatively. The serum leptin, zinc, and copper levels were studied. RESULTS: In group n(1) circulating leptin levels were significantly increased at T2 when compared to T0 and T1 (p < 0.05); zinc levels were decreased at T2 when compared to T0 and T1 (p < 0.05); copper levels were decreased at T2 when compared to T0 (p < 0.05), and decreased at T1 when compared to T0 (p < 0.05). In group n(2) circulating leptin levels were significantly increased at T2 when compared to T0 and T1 (p < 0.05); zinc levels were decreased at T2 when compared to T0 and T1 (p < 0.05); copper levels were increased at T2 when compared to T1 (p < 0.05). CONCLUSIONS: These results indicate that circulating leptin levels increase after the extracorporeal circulation as an acute response, while zinc and copper levels decrease at the same period. Preoperative zinc administration does not prevent the leptin response after extracorporeal circulation.
Keywords: extracorporeal circulation; leptin; zinc; copper